Comprehensive prognostic and immunological analysis of CCT2 in pan-cancer - Lv, Wenming; Shi, Lin; Pan, Jiebing; Wang, Shengbao (Frontiers in Oncology, 2022)
CCT2 acts as a molecular chaperone protein that assists in the proper folding of proteins, thus ensuring a dynamic balance of cellular homeostasis. Despite the increasing evidence supporting the important role of CCT2 in the tumorigenesis of certain cancers, few articles have been published to provide a systematic pan-cancer analysis of CCT2. Hence, to evaluate the expression status and prognostic significance of CCT2 in pan-cancers. An analysis of the relationship between CCT2 and different tumor immune cell infiltrations was conducted using datasets from the Cancer Genome Atlas, Cancer Cell Lineage Encyclopedia and so on. In most cancers, CCT2 expression was high and was associated with poor prognosis. Moreover, CCT2 gene expression was negatively correlated with infiltration of most immune cells in 10 cancer types, and CCT2 expression was related to tumor mutation burden (TMB) and microsatellite instability (MSI). The role that CCT2 plays in tumorigenesis and tumor immunity suggests that it can serve as a prognostic marker in many cancers.